Sociodemographic characteristics and risk factors of hepatitis B and C among Iraqi health care workers - Al-Mashhadani, Jalil I.; Al-Hadithi, Tariq S.; Al-Diwan, Jawad K.; Omer, Ali R. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Many workers have described the prevalence of HBV markers and anti-HCV among selected populations including health care personnel in Iraq. The purpose of this study is to describe the demographic characteristics and risk factors of hepatitis B and C in a sample of Iraqi health care workers (HCWs).Materials and methods: A total of 1656 HCWs selected from Baghdad city was included in this study. A questionnaire form was filled for each HCW by direct interview. The data requestedincluded demographic characteristics and risk factors of exposure to HBV and HCV. HCWs were screened for the presence of HBsAg, anti-HBs and anti-HCV.Results: A higher prevalence of HBsAg, anti-HBs and anti-HCV was demonstrated among males (7.8%, 44.7% and 2.13%, respectively) than females (3.3%, 34.8% and 0.99%, respectively). The HBsAg carrier rates were decreasing with advancing age, while anti-HBs and anti-HCV showed an increase with advancing age. A higher rate of HBsAg, anti-HBs and anti-HCV was detected among HCWs from low socioeconomic level than those from high socioeconomic level. Health personnel who had a personal history of hepatitis were more likely to be HBsAg positive than those without such a risk factor and HCWs with personal or family history of hepatitis were more likely to have anti-HBs than those without such risk factors. Health personnel with personal history of hepatitis or blood transfusion had significantly higher prevalence of anti-HCV when compared with thosewithout such risk factors.Conclusion: This study indicates that non-paranteral route is the major route of transmission of HBV infection, while paranteral route is the major route for transmission of HCV among the health personnel.